(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
Morphological characters of seeds from 23 Cassia L. sensulato species from Sudan were examined with the aid of StereoMicroscope in order to clarify their taxonomic status. The seeds of allmembers of the genus Senna (with the exception of S. bicapsularis) wereareolate, whereas the seeds of Cassia sensu stricto and Chamaecristaspecies were not areolate and the shapes of the latter two genera wereovate-elliptic and rhombic, respectively. The seeds are described, anindented identification key is presented, and the unique taxonomicposition of S. bicapsularis is discussed. The results supported the divisionof the genus Cassia L. sensu lato into three allied genera (Cassia sensustricto, Chamaecrista and Senna).